Grain growth control in Nb-doped BaTiO3 - Brzozowski, E. (2005)
In this work, the grain growth inhibition effect of Nb2O5 on BaTiO3 was improved by employing selected raw materials and an advanced milling technique. BaTiO3 prepared from crystalline TiO2 powder and needle-shaped BaCO3 led to large grains on sintering, in addition to second phases due to Ti segregation and non-complete Nb incorporation. These phases did not inhibit grain growth but they affected the permittivity–temperature dependence of the material. In these materials, compensation charge mechanisms by electrons provided semiconducting characteristics at room temperature. Further modifications on materials selection and ceramic processing varied the Nb incorporation extent significantly. Mechanochemically activated BaCO3 reactant and ultrafine TiO2 led to an early reaction. It provided a wide temperature range for Nb5+ incorporation as the BaCO3–TiO2 reaction progressed. Complete, homogeneous Nb incorporation in these materials allowed a strong grain growth inhibition on sintering and avoided accumulation of needle-shaped phases. Simultaneously to the grain growth inhibition phenomenon a considerable increase in titanium vacancy concentration was detected. Resulting materials stabilized in a pseudocubic phase and showed high dielectric features at room temperature.